2015
DOI: 10.1002/ana.24444
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations in the MTOR gene cause focal cortical dysplasia type IIb

Abstract: We found low-prevalence somatic mutations in MTOR in FCD type IIb, indicating that activating somatic mutations in MTOR cause FCD type IIb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
170
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(188 citation statements)
references
References 42 publications
6
170
0
4
Order By: Relevance
“…TSC is naturally a mutation of either TSC1 or TSC2 in 85%, whereas more than half of those cases show also mosaicism 43. Recent studies found somatic (mosaic) mutations affecting the mTOR signaling also in focal lesions of FCD II patients 4, 8, 21, 25, 32, 36. This is a very important aspect since as far as we know, in FCD, the mutations are localized and show profound variability in cellular expression.…”
Section: Discussionmentioning
confidence: 99%
“…TSC is naturally a mutation of either TSC1 or TSC2 in 85%, whereas more than half of those cases show also mosaicism 43. Recent studies found somatic (mosaic) mutations affecting the mTOR signaling also in focal lesions of FCD II patients 4, 8, 21, 25, 32, 36. This is a very important aspect since as far as we know, in FCD, the mutations are localized and show profound variability in cellular expression.…”
Section: Discussionmentioning
confidence: 99%
“…Because the molecular genetic etiology of FCD has remained elusive, genetically validated drug targets in individuals with FCD are poorly understood. Recently, we and another group have shown that somatic activating mutations in MTOR (MIM: 601231) in the brain account for 15%-25% of individuals with FCDII 8,9 and that inhibition of hyperactivated mTOR kinase reverses epilepsy and the development of cytomegalic neurons. 8 However, the genetic causes underlying the development of FCDII in individuals who are negative for MTOR mutations remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, somatic mutations have been associated with hyperactivation of the mTOR pathway in FCD type II 9, 10, 11, 12. In our cohort, 28.5% of the tested patients harbored brain somatic mutations in genes belonging to the mTOR pathway.…”
Section: Discussionmentioning
confidence: 74%
“…The somatic missense mutations identified in MTOR and TSC2 are probably deleterious, because they are classified as damaging, by 2 (Polyphen2 and SNPs&GO) of the 3 mutation prediction programs used. In addition, rs1057519779 in MTOR has been previously reported in patients with FCD type II 21. Variation identified in AKT1 is a glutamic acid in‐frame deletion.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation